Neighbourhood disadvantage and child behaviour in Montevideo, Uruguay: a mixed methods study - Seth Frndak, MA; Yanina Gallo, BA; Elena Quierolo, MD; Gabriel Barg, PhD; Nelly Mañay, PhD; Katarzyna Kordas, PhD (Elsevier, 2020)
Background: The neighbourhood context is important for child development, but little evidence exists on neighbourhood-based challenges and resources in South American cities. We used a mixed methods approach to quantify the effect of neighbourhood disadvantage on child behaviour and to empower parents to explain life in disadvantaged neighbourhoods in Montevideo, Uruguay. Methods: A study within the Salud Ambiental Montevideo (SAM) longitudinal cohort yielded a cross-sectional sample of 225 (63% of total) children aged 6-8 years with complete data. Teacher ratings of child behaviour were collected using the Connors' Teacher Rating Scale-Revised (CTRS-R) and Behavior Rating Inventory of Executive Function (BRIEF). Five indicators of neighbourhood disadvantage were collected from Montevideo census data, and combined into to a single neighbourhood disadvantage factor. In the analyses of the relation between neighbourhood disadvantage and child behaviour scores we controlled for individual-level socioeconomic indicators, child IQ, and concentrations of lead in blood. In a nested study, we conducted semi-structured interviews with ten caregivers of SAM children in low-income neighbourhoods. Parents discussed what neighbourhood means to them and what they liked and disliked about their neighbourhood, perceptions of community services, and raising children in their neighbourhood. Parents were also asked to photograph their neighbourhoods and to discuss the meaning of at least four of their photographs during the interview. Findings: One SD increase in neighbourhood disadvantage was related to a 1% increase in prevalence ratio on scores of oppositional behaviour (p=0·048) and a 4% increase in prevalence ratio on emotional control problem ratings (p=0·006). Neighbourhood disadvantage was unrelated to hyperactive behaviours and inhibitory control scores. From the interviews, common themes emerged on the importance of playgrounds, neighbourhood disorder, fears over crime, and lack of infrastructure. Many interviewees perceived that their neighbourhoods had been safer in the past. Suggestions for improving neighbourhoods included: better waste management, increased policing, traffic regulation, and improved local clinics. Interpretation: Neighbourhood disadvantage is related to child behaviour beyond the influences of individual-level socioeconomic factors. Low-income neighbourhoods in Montevideo face challenges related to local infrastructure and services. Parents advocated for improved infrastructure, health services, transportation, and safety. Future studies should test specific mechanisms behind the effects of neighbourhood disadvantage and child behaviour in Montevideo. Funding: US National Institute of Environmental Health Sciences (NIEHS) and Fogarty International (FI) Institute under grant number R21ES16523, and by NIEHS grant R21ES019949.